FACTORS INFLUENCING YOUNG FEMALE PURCHASE INTENTION TOWARDS LOCAL COSMETICS PRODUCT IN MALAYSIA - Nik Noorhazila Nik Mud; Norfazlirda Hairani; Aimi Nadia Ibrahim@Zakaria; Mardhiah Kamaruddin; Hazriah Hasan (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
This paper aimed to study the effect between attitude, brand awareness, consumer experiences and price on young female purchase intention towards local cosmetic products in Malaysia. The main factor of consumer behaviour that used in this study was to analyse customer female purchase intention were attitude, brand awareness, consumer experience, and price. We used a survey questionnaire to collect 226 valid responses from a female student of Bachelor of Entrepreneurship (Retailing) with Honours in UMK. These collected data were analysed using Statistical Package for Social Science (SPSS) version 24 and the result gathered through the Pearson Correlation Coefficient and Multiple Regression. The findings revealed that attitude, brand awareness, consumer experiences, and price emerged with a significant influence on female intention toward local cosmetics among young female consumers. The implication from this study is for the female consumer who is wearing a cosmetic product, an industry or organization who involve in produce local cosmetic product and retailer who sale a local cosmetic product. Finally, the result shows that attitude influences young female purchase intention the most compared to brand awareness, consumer experiences, and price.